The consistency of Thrasymachus’ theses on justice in Plato’s Republic I (Revista Archai, 2020)
The discussion between Thrasymachus and Socrates in Book I of Plato's Republic instead the question about justice started with Cephalus. Thrasymachus is an important character, who relates justice to the city government. This causes justice to leave individual sphere and enter public sphere. In our article, we want to verify how Thrasymachus' theses on justice and whether they are consistent with each other. The problem of consistency of theses is old among commentators and presents different solutions. Our intention is to propose a solution to the problem and to relate this to art of government proposed by Thrasymachus. This allows us to verify the manner in which Socrates and Thrasymachus differ in their proposals for government and types of ruler. In this way, our work intends to contribute with literature on the role played by Thrasymachus in Plato’s work.